Task dependent changes in mechanical and biomechanical measures result from manipulating stiffness settings in a prosthetic foot. (October 2021) - Ármannsdóttir, Anna L.; Lecomte, Christophe; Brynjólfsson, Sigurður; Briem, Kristín
Abstract: Background: Adaptation of lower limb function to different gait tasks is inherently not as effective among individuals with lower limb amputation as compared to able-bodied individuals. Varying stiffness of a prosthetic foot may be a way of facilitating gait tasks that require larger ankle joint range of motion. Methods: Three stiffness settings of a novel prosthetic foot design were tested for level walking at three speeds as well as for 7, 5° incline and decline walking. Outcome measures, describing ankle range of motion and ankle dynamic joint stiffness were contrasted across the three stiffness settings. Standardized mechanical tests were done for the hindfoot and forefoot. Findings: Dorsiflexion angle was incrementally increased with a softer foot and a faster walking speed / higher degree of slope. The concurrent dynamic joint stiffness exhibited a less systematic change, especially during INCLINE and DECLINE walking. The small difference seen between the stiffness settings for hindfoot loading limits analysis for the effects of stiffness during weight acceptance, however, a stiffer foot significantly restricted plantarflexion during DECLINE. Interpretations: Varying stiffness settings within a prosthetic foot does have an effect on prosthetic foot dynamics, and differences are task dependent, specifically in parameters involving kinetic attributes. When considering the need for increased ankle range of motion while performing more demanding gait tasks, a foot that allows the users themselves to adjust stiffness according to the task at hand may be of benefit for active individuals, possibly enhancing the user's satisfaction and comfort during various daily activities. Highlights: Three stiffness settings were analyzed with a novel prosthetic foot design. Dynamic Joint Stiffness can provide insight into a prosthetic foot's dynamics. Prosthetic foot dynamics and characteristics during gait are task dependent. Mechanical data does not capture the prosthetic foot's dynamics across gait tasks. Studies of long-term effects of stiffness change and users´ preferences are needed.